Power tool use in orthopaedic surgery: iatrogenic injury, its detection and technological advances - Arnold,M; Zhao,S; Doyle,R; Jeffers,J; Boughton,O (JBJS Open Access, 2021)
Background: Power tools are an integral part to orthopaedic surgery but have the capacity to cause iatrogenic injury. This systematic review aimed to investigate the prevalence of iatrogenic injury due to power tools in orthopaedic surgery and discuss the current methods 9that can be used to reduce this. Methods: A systematic review of all English language articles using a keyword search was undertaken in Medline, Embase, PubMed and Scopus databases. Exclusion criteria included injuries related to cast saw, temperature induced damage and complications not clearly related to power tool use. Results: 3694 abstracts were retrieved, and 88studies were included in the final analysis. Only a few studies and individual case reports directly looked at prevalence of injury due to power tools. This included 2 studies looking at frequency of vascular injury during femoral fracture fixation (0.49% and 0.2%),2 studies investigating frequency of vertebral artery injury during spinal surgery (0.5% and 0.08%)and 3 studies investigating vascular injury during total joint arthroplasty (124 vascular injuries involving 138 blood vessels,0.13% and 0.1% incidence)in addition to 1 questionnaire sent electronically to surgeons. There are multiple methods to prevent damage during the use of power tools. These include robotics, Revised Manuscript (Maximum 3000 Words)simulation, specific drill settings and real-time feedback techniques such as spectroscopy and electromyography. Conclusion: Power tools have the potential to cause iatrogenic injury to surrounding structures during orthopaedic surgery. Fortunately, the published literature suggests the frequency of iatrogenic injury using orthopaedic power tools is low. There are multiple technologies available to reduce damage using power tools. In high-risk operations the use of advanced technologies to reduce the chance of iatrogenic injury should be considered. Clinical Relevance: Power tools used during orthopaedic surgery have the potentia